Sport og national identitet. J.P. Müller og dansk roning ca. 1880-1900 - Bonde, Hans (Historisk Tidsskrift, 2022)
Sports and National Identity: J.P. Müller and Danish Rowing ca. 1880–1900 Since its birth in Great Britain at the end of the 18th century, modern sports has played a growing part in nation-building. Nevertheless, Danish sportsmen during the last two decades of the 19th century were sometimes looked upon with incredulity, not least because of their minimal clothes. With leading Danish amateur sportsman, J.P. Müller, as an important source of inspiration, the earliest cultivation of national identity rooted in sports started in amateur rowing. Danish sports was heavily influenced by English coaches, rules, equipment, and technical terms, demonstrating the ability of sports to exemplify progress based on scientific measurement of times, distances, and records. Over time, the pioneer teams in rowing were represented not only by handpicked club teams, but by assemblages of the very best sportsmen from all over the country, dressed in national team jerseys in Danish colours, defending the nation’s honour in confrontation with foreign countries on the water, the natural habitat of the Danish island realm. Rowing offered the possibility of defeating athletes of the Scandinavian sister nations and, even more alluringly, the German Empire. A distinguished Danish position on the map of international sports might serve as a symbolic act of revenge after the military defeat in 1864. The ability of early sports to bind the nation together was seen, for example, by the fact that young sportsmen who migrated from rural to urban communities quickly found training facilities and competition opportunities in the clubs. Also, sports clubs from all parts of the country met each other in domestic tournaments, competing for a national trophy: The Danish Championship. However, sports was not only nationally unifying; sometimes its associations embodied political differences, for instance regarding the issue of parliamentarianism as constitutional practice.